Pleural Effusion: A Rare Side Effect of Nilotinib—A Case Report - Hava Üsküdar Teke; Olga Meltem Akay; Deniz Gören Şahin; Mustafa Karagülle; Eren Gündüz; Neslihan Andıç (Case Reports in Medicine)
Pleural effusion, as a side effect of tyrosine kinases, may be seen as most commonly associated with dasatinib and very rarely seen with nilotinib. In this report we present a chronic phase of CML case that was treated with nilotinib due to imatinib (Gleevec) allergy and had pleural effusion with nilotinib at 5th year of treatment. If pleural effusion develops in patients taking nilotinib and if this effusion is exudative and lymphocyte predominant, after ruling out pulmonary and cardiac etiologies, it must be associated with nilotinib; according to stage of effusion drug should be discontinued and/or steroid should be started and/or surgery should be performed.